Hakikat Masyarakat dalam Perspektif Filsafat Pendidikan Islam - Abdul Rozak Ali Maftuhin; Faridi Faridi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The Philosophy of Islamic Education serves as the cornerstone of knowledge. Society is often depicted as a collection of individuals who share common characteristics and goals. In Islam, every member of society enjoys equal rights and responsibilities. Islam rejects caste systems and the allocation of special privileges to any individual or group; the honor of a person in Islamic society is determined solely by their devotion to Allah. Typically, an Islamic society is characterized by three main features: orientation towards Allah, prioritization of piety, and mutual respect among its members. The essential elements for building an Islamic society include Brotherhood, Compassion, Equality, Freedom, and Social Justice. The connection between the philosophy of Islamic education and society is very close, forming an inseparable symbiosis. Consequently, Islamic society plays a crucial role and bears a significant responsibility in shaping complete Muslims and fostering a civil and ideal Islamic community, in alignment with the teachings of the Qur'an and the Sunnah.